Doctoral virtual writing groups: a dialogical proposal for the learning of literacy practices (Praxis Educativa, 2024)
From a sociocultural perspective that regards dialogue as a means for knowledge construction, writing groups can facilitate the learning of literacy practices. However, there is limited research on dialogues within these groups, particularly those dedicated to doctoral theses. This study examines interactions in two virtual doctoral writing groups, focusing on oral exchanges among participants to determine if they favored the construction of knowledge related to literacy practices. We found that both groups primarily emphasize revision, suggesting the proposed task's relevance. Differences in the quantity, extent, and quality of dialogues centered on knowledge construction were identified, possibly due to participants' prior feedback experiences, meeting and draft durations, coordination, and the importance assigned to oral feedback. These findings may guide future initiatives to support literacy practices in postgraduate education.
Keywords: writing circles, dialogism, postgraduate, feedback, academic writing